Pembentukan Teamwork dengan Metode DBScan untuk Meningkatkan Kinerja Karyawan - Tarigan, Feriani Astuti; Hoki, Leony (Universitas Methodist Indonesia, 2024)
CV. Surya Jaya Security System is a private company in the city of Medan that is engaged in the security system, which sells various brands of attendance machines, CCTV and accessories and doorstops, as well as various types of other security equipment. In doing work every day, it takes several employees who work together in completing the work of the customer. In one day, CV. SJSS can accept orders from several customers at once. Therefore, it is necessary to make arrangements for the formation of a work team (teamwork) to complete the work, so that all orders are completed on time and still maintain the quality of service from these employees. To carry out the process of grouping these employees, the data grouping method can be applied or often referred to as the clustering method. Density-Based Spatial Clustering Algorithm with Noise (DBSCAN) is one of the pioneering examples of the development of density-based clustering techniques or commonly known as density-based clustering. The result of this research is a website for the formation of teamwork by applying the DBSCAN method which is able to group employees, so as to improve employee performance.